Respuesta :
Actually, this answer would be true. Why?
The first equation is: a(sub n) = 8, 13, 18, 23
The second is: a(sub 1)=8 ; a(sub n)= a(sub n-1)+5
if you wish to find the second term, plug two into the equation for n
8+5=13
to find the third, plug the second term, 13, in for n.
13+5=18.
Hope this helped! I know it's a bit on the late side, but at least you can get the general idea!
The first equation is: a(sub n) = 8, 13, 18, 23
The second is: a(sub 1)=8 ; a(sub n)= a(sub n-1)+5
if you wish to find the second term, plug two into the equation for n
8+5=13
to find the third, plug the second term, 13, in for n.
13+5=18.
Hope this helped! I know it's a bit on the late side, but at least you can get the general idea!